Escaping poverty traps?: Collective action and property rights in post-war rural Cambodia - Weingart, Anne; Kirk, Michael (International Food Policy Research Institute, 2008)
This paper introduces and applies an analytical framework to study how formal and informal institutions influence socio-economic change and poverty reduction in rural Cambodia, giving specific reference to property rights and collective action. It focuses on emerging endogenous mechanisms of cooperation as well as on the role of external actors and instruments in forming or enhancing collective action institutions, and enforcing use and ownership rights among the rural poor. Within this framework key contextual factor, such as asset endowments, legal structures, and power relations, have an impact on poverty and rural livelihoods, but are also mediated and changed by property right regimes and local cooperation. Findings indicate that access to and use of natural capital still contributes significantly to rural incomes. Access to natural resources is, however, defined by multiple and overlapping rights, both private and common ones, which are, in turn, governed by formal and informal patterns of cooperation. Collective action also contributes to improve livelihoods. Nevertheless, depending on asset endowments, differences exist in the degree of participation. Owing to Cambodia?s recent history of genocide, forced collectivization and resettlement, property rights regimes have been severely affected, remain contested, and are re-established only slowly. In this context, the mutual trust necessary for successful cooperation in common property issues is severely undermined.